Gender equality and women's happiness in post-apartheid South Africa. Issue 2 (3rd April 2021) - Rustin, Carmine; Florence, Maria
Abstract: Voice, agency, access to resources, realising one's potential, sharing of responsibilities are some of the meanings women attach to gender equality. Yet, at the same time, women espouse patriarchal heteronormative views about gender. What does this mean for the South African government's efforts for gender equality, in the context of the gendered legislation it has enacted, as well as the Beijing Platform for Action. Additionally, have these efforts shifted the realities of women and has it improved the subjective well-being or happiness of women? Framed within a feminist epistemological and methodological approach and drawing on the results from a mixed methods study, this article explores the meanings women attach to gender equality and whether they link gender equality to their subjective well-being. Individual interviews were conducted with key informants and focus groups with women not involved in the gender sector. Data from the World Values Survey was used to investigate whether there is a correlation between the values that participants attach to gender equality and happiness. The study reveals a complex relationship between gender, race, class and happiness. Another key finding is that women value gender equality as an essential feature of democracy. We also see that while most women hold progressive views on gender equality, these are not always clear-cut. While the views of South African women range from progressive to conservative, individual viewpoints are much more nuanced and complex. This article highlights some policy and scholarship implications for gender equality and happiness research and interventions.